2021
DOI: 10.3390/v13061162
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Hepatotropic Viruses in Cats: A Brief Review

Abstract: The possible role of viruses in feline liver disease has long remained neglected. However, in 2018, an analogue of human hepatitis B virus was identified in cats. Moreover, antibodies for human hepatitis E have been detected consistently at various prevalence rates in cats. Although the correlation between these viruses and the liver injury in cats must be clarified, hepatotropic viruses might represent an increasing risk for feline and public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Although there was a small increase of AST and ALT in cats, it is considered to be specific to liver injuries due to the limited short half‐life 18,19 . Because the alterations of liver parenchyma that lead to increased liver enzymes have been associated with multifactorial causes such as infections or other systemic diseases, 20 even though we attempted to rule out other hepatotropic viruses 7 and other systemic causes, the definitive association of DCH presentation and increased liver enzymes presented in this study still warrants further investigations. We also found that the LVCN had a positive correlation with an increase of ALT and GGT, which precedes increases in ALP and is considered a more sensitive indicator for liver disease in feline species.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although there was a small increase of AST and ALT in cats, it is considered to be specific to liver injuries due to the limited short half‐life 18,19 . Because the alterations of liver parenchyma that lead to increased liver enzymes have been associated with multifactorial causes such as infections or other systemic diseases, 20 even though we attempted to rule out other hepatotropic viruses 7 and other systemic causes, the definitive association of DCH presentation and increased liver enzymes presented in this study still warrants further investigations. We also found that the LVCN had a positive correlation with an increase of ALT and GGT, which precedes increases in ALP and is considered a more sensitive indicator for liver disease in feline species.…”
Section: Discussionmentioning
confidence: 85%
“…The extracted nucleic acids deriving from the abovementioned blood and liver samples were initially screened for concomitant viral infections that have been associated with liver damage in cats, 7 including feline retroviruses (feline immunodeficiency virus [FIV] and feline leukemia virus [FeLV]), feline calicivirus (FCV), and feline coronavirus (FCoV), using 1‐step reverse‐transcription (RT)‐PCR (QIAGEN OneStep RT‐PCR Kit, Qiagen GmbH, Hilden, Germany) 8 . The samples that were PCR‐positive for any screened viruses were discharged from this study (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Our phylogenetic analysis results showed that all positive samples obtained from domestic cats from Türkiye localized into Orthohepadnavirus genus. These findings raise the question of whether DCH can affect other domestic (Capozza, Decaro et al, 2021;Capozza et al, 2023;Choi et al, 2022;Diakoudi et al, 2022) or wild carnivores. We believe that future studies investigating hepadnaviruses in different carnivorous species are needed to understand the origin of DCH and its relationship with other species.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, viruses genetically close to the Australian DCH strain have been detected in cat whole blood and serum samples with rates of 10.8% in Italy (Lanave et al., 2019), 12.4% in Thailand (Piewbang et al., 2020), and 12.3% in Malaysia (Anpuanandam et al., 2021). The potential clinical impact of DCH on feline health and its possible role in the development of liver disease is currently under investigation (Capozza, Decaro, et al., 2021). A positive correlation between an increased level of markers indicative of structural or functional liver damage and high serum viral loads (>10 4 genome copies per millilitre) has been observed (Lanave et al., 2019; Capozza, Lanave, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%